A procalcitonin-guided algorithm to reduce antibiotic duration. Issue 6 (November 2016) - Thayer, Sharice
Abstract : Abstract: With the rise in antimicrobial resistance, it is imperative that healthcare providers monitor and regulate antibiotic therapy more closely. Antimicrobial resistance can lead to increased morbidity, mortality, and healthcare expenditures. Current research suggests a procalcitonin-guided algorithm can assist healthcare providers in deciding the appropriate antibiotic therapy duration in critical care patients with sepsis. Utilizing this algorithm in practice can reduce unnecessarily lengthy antibiotic durations, improve patient outcomes, and decrease hospital length of stay and expenditures. Abstract : Current research suggests a procalcitonin-guided algorithm can assist healthcare providers in deciding the appropriate antibiotic therapy duration in critical care patients with sepsis.